2018
DOI: 10.1002/cpdd.473
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Hydrochloride at Steady State Lacks Clinically Relevant QTc Interval Increases in Healthy Adults

Abstract: We evaluated the effects of therapeutic and supratherapeutic doses of tramadol hydrochloride on the corrected QT (QTc) interval in healthy adults (aged 18-55 years) in a randomized,phase I,double-blind,placebo-and positive-controlled, multiple-dose, 4-way crossover study. Participants were randomized to receive 1 of 4 treatments (A-D), 1 each in 4 treatment periods (1-4), separated by a washout period (7-15 days). Treatment A comprised tramadol 400 mg (therapeutic dose) on days 1 through 3, tramadol 100 mg and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Important to note, buprenorphine, fentanyl and alfentanil could be used as a valid alternative to morphine in opioid rotation in ribociclib-treated patients since no QTc prolongation-related issues were reported for these drugs [48]. No QTc effects were observed at supratherapeutic doses of the opioid/ nonopioid analgesics tramadol [50] and tapentadol [51].…”
Section: Pharmacodynamic-based Ddismentioning
confidence: 99%
“…Important to note, buprenorphine, fentanyl and alfentanil could be used as a valid alternative to morphine in opioid rotation in ribociclib-treated patients since no QTc prolongation-related issues were reported for these drugs [48]. No QTc effects were observed at supratherapeutic doses of the opioid/ nonopioid analgesics tramadol [50] and tapentadol [51].…”
Section: Pharmacodynamic-based Ddismentioning
confidence: 99%
“…25 The study using supra-therapeutic doses of tramadol in health volunteers showed a relatively high proportion of patients suffering from hiccups, suggesting that this adverse reaction might be dose related. 12 Accordingly, of the 50 available cases in EudraVigilance, the dose of tramadol was ⩾150 mg/day in 24 cases (48%) and <150 mg/ day in 17 cases (dose was unknown for 9 cases).…”
Section: Discussionmentioning
confidence: 99%
“…This proportion was higher in those on 600 mg/day, with 7.8% of them suffering from hiccups. 12 The third clinical trial compared the efficacy and safety of tramadol versus fentanyl in pediatric patients undergoing upper gastrointestinal endoscopy. Patients were divided into three subgroups: 0-2 years, 2-12 years, and >12 years.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…With the exception of methadone, which has been shown to cause QTc prolongation [140][141][142][143][144][145][146][147][148] and is strongly associated with TdP (at doses as low as 40 mg/day) [140][141][142] , most opioids used in the perioperative setting have no effect on QTc when used at clinically relevant doses. This is true for fentanyl 149,150 , alfentanil 151 , remifentanil 149,152,153 , morphine 139 , and tramadol 139,154 .…”
Section: Opioidsmentioning
confidence: 97%